(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
This contribution introduces and summarises the papers received in response to the call for papers Beyond Illness: New Understandings of Health and the Law. The call, launched by the Editorial Board to introduce the first issue of the Bio-Law Journal, is focused on the ever changing definitions of health and disease and on the increasing number of medical interventions required even in the absence of a pathological status. This paper recalls the process of evolution of the right to health and offers some insights about some new shapes it gained in recent years.